Using Quantitative Research Methods to Determine the Validity and Reliability of an Undergraduate Citation Rubric - Angell, Katelyn (Qualitative and Quantitative Methods in Libraries, 2017)
Since the beginning of the 2000s academic librarians have been developing and using scoring rubrics to assess various facets of student learning within the library instruction classroom. There are numerous advantages to evaluating student learning outcomes with rubrics. These benefits include the capability to evaluate student work over time or across academic subjects, a method of offering students constructive, objective feedback, and an opportunity for library colleagues to create a unified, standardized evaluation tool. Currently there are many articles within Library and Information Science literature detailing the adoption of rubrics into the academic library classroom. However, there is little research within the field pertaining to reliability and validity analyses of these rubrics. In order to ensure that a rubric consistently measures student learning comprehension it is important to perform these quantitative calculations on it prior to widespread use. The present study describes a project the author completed to measure reliability and validity of a rubric developed to assess the citing and referencing knowledge of undergraduate students at a large university in New York City.